Co-targeting of Bcl-2 and mTOR pathway triggers synergistic apoptosis in BH3 mimetics resistant acute lymphoblastic leukemia - Iacovelli, Stefano; Ricciardi, Maria Rosaria; Allegretti, Matteo; Mirabilii, Simone; Licchetta, Roberto; Bergamo, Paola; Rinaldo, Cinzia; Zeuner, Ann; Foá , Robin; Milella, Michele; McCubrey, James A.; Martelli, Alberto M.; et al. (My University, 2015)
Several chemo-resistance mechanisms including the Bcl-2 protein family overexpression and constitutive activation of the PI3K/Akt/mTOR signaling have been documented in acute lymphoblastic leukemia (ALL), encouraging targeted approaches to circumvent this clinical problem. Here we analyzed the activity of the BH3 mimetic ABT-737 in ALL, exploring the synergistic effects with the mTOR inhibitor CCI-779 on ABT-737 resistant cells. We showed that a low Mcl-1/Bcl-2 plus Bcl-xL protein ratio determined ABT-737 responsiveness. ABT-737 exposure further decreased Mcl-1, inducing apoptosis on sensitive models and primary samples, while not affecting resistant cells. Co-inhibition of Bcl-2 and the mTOR pathway resulted cytotoxic on ABT-737 resistant models, by downregulating mTORC1 activity and Mcl-1 in a proteasome-independent manner. Although Mcl-1 seemed to be critical, ectopic modulation did not correlate with apoptosis changes. Importantly, dual targeting proved effective on ABT-737 resistant samples, showing additive/synergistic effects. Together, our results show the efficacy of BH3 mimetics as single agent in the majority of the ALL samples and demonstrate that resistance to ABT-737 mostly correlated with Mcl-1 overexpression. Co-targeting of the Bcl-2 protein family and mTOR pathway enhanced drug-induced cytotoxicity by suppressing Mcl-1, providing a novel therapeutic approach to overcome BH3 mimetics resistance in ALL.
Keywords: acute lymphoblastic leukemia; targeted therapies; BH3 mimetic resistance; mTOR inhibition; Mcl-1